Family perception of the impact of Dengue: Knowledge, Attitudes and Practices. - Salamanca-Ramos, Emilce; León Alfonso, Graciela Astrid; Baquero Álvarez, Nelson (Enfermería Global)
Introduction: Vector-borne diseases are among the leading causes of comorbidity in the Latin American population, especially dengue. Objective: To determine the management of dengue from the perspective of knowledge, attitudes and practices of families in two municipalities located in the department of Meta-Colombia. Materials and Methods: A quantitative paradigm, non-experimental descriptive, observational, cross-sectional design study with probabilistic, two-stage, stratified sampling with a sample of 3,703 families in their homes. A sociodemographic survey and a Knowledge, Attitudes, and Practices (KAP) instrument on dengue were applied. Information was processed using SPSS® ver. 20, Excel, and Word. Results: The study shows a medium knowledge index (44.6%), a low attitudes index (50.8%), and a high practices index (93.1%). No statistically significant association was found among gender and the knowledge (p = 0.995) and practices (p = 0.696) indices; a statistically significant association was found among age groups and knowledge (p = 0.000) and attitudes (p = 0.002) indices. Conclusions: Social actors have knowledge about the symptoms and management of the disease, but no recognition of the fatality risk of the disease. Families are more receptive to preventive practices when they have had a member experience the disease. Regarding gender participation in environmental care and disease control, women are more active in collective dengue control efforts.